Analysis of Factors Related To Quality of Life in Chronic Kidney Disease Patients Undergoing Hemodialysis: A Cross-Sectional Study - Aurellia Firstania; Mesya Mesya (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract Chronic kidney disease (CKD) and hemodialysis (HD) therapy can reduce quality of life due to the burden of symptoms, activity limitations, and psychological and social problems. This study aims to analyze factors associated with quality of life in CKD patients undergoing HD at Sekayu Regional Hospital. A descriptive-analytical survey with a cross-sectional design was conducted among 44 respondents purposively selected from May 1 to June 1, 2025. Quality of life was measured using the WHOQOL-BREF and categorized into good and poor based on the median total score. Bivariate analysis used the chi-square test, while multivariate analysis used multiple logistic regression. The results showed that the majority of respondents were aged >45 years (56.8%), male (52.3%), and on HD for <2 years (77.3%). There was a significant association between age (p=0.001), gender (p=0.002), and duration of HD (p=0.004) with quality of life. Education (p=0.523), marital status (p=0.624), employment (p=0.510), and income (p=0.319) were not associated. Logistic regression showed that age >45 years was the dominant factor associated with a lower odds of good quality of life (p=0.024; OR=0.089). Comprehensive nursing interventions are needed, especially for elderly and female patients, to improve the quality of life during HD.